2013
DOI: 10.1007/s11738-013-1332-8
|View full text |Cite
|
Sign up to set email alerts
|

Fruit skin color and the role of anthocyanin

Abstract: Fruit skin coloration is a unique phase in the life cycle of fruiting plants and is mainly attributed to anthocyanin pigments. Anthocyanins are the largest and most diverse group of plant pigments derived from the phenyl propanoid pathway. They are water-soluble phenolic compounds that form part of a large and common group of plant flavonoids. Coloration encompasses several physiological and biochemical changes that happen through differential expression of various developmentally regulated genes. Due to resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 56 publications
(47 reference statements)
6
68
0
2
Order By: Relevance
“…Horticulturists have long been interested in breeding different varieties of plants with fruits having bright colours, saturated hues, sweet taste and high nutritional value, among which attractive fruit colour is one of the most desirable horticultural traits (Kayesh et al , ; Pillet et al , ). The quantity and variability of flavonoids control strawberry fruit coloration in both wild diploid and cultivated octoploid strawberry varieties (Lin‐Wang et al , ; Schaart et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Horticulturists have long been interested in breeding different varieties of plants with fruits having bright colours, saturated hues, sweet taste and high nutritional value, among which attractive fruit colour is one of the most desirable horticultural traits (Kayesh et al , ; Pillet et al , ). The quantity and variability of flavonoids control strawberry fruit coloration in both wild diploid and cultivated octoploid strawberry varieties (Lin‐Wang et al , ; Schaart et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Hotta et al (1997a) showed that 5-ALA could regulate the synthesis of chlorophyll; this might have been the reason why it could not promote the degradation of pericarp chlorophyll. However, 5-ALA could significantly promote anthocyanin accumulation in litchi pericarp, and fruit skin coloration was mainly attributed to anthocyanin pigments (Kayesh et al, 2013). Therefore, 5-ALA might regulate litchi fruit coloring mainly by controlling anthocyanin synthesis, rather than by causing the degradation of chlorophyll.…”
Section: Discussionmentioning
confidence: 98%
“…Many enzymes are involved in anthocyanin biosynthesis, such as phenylalanine ammonia lyase (PAL), chalcone isomerase (CHI), dihydroflavonol-4-reductase (DFR), anthocyanidin synthase, and flavonoid-3-O-glucosyltransferase (UFGT; Kayesh et al, 2013;Petroni and Tonelli, 2011). Wang et al (2004b) indicated that the activities of PAL, CHI, and DFR had no effect on anthocyanin content in litchi pericarp, but UFGT was closely related to anthocyanin content during the maturation of 'Feizixiao' litchi fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of the natural products has improved due to the global development of maintaining good health and reducing the risk of disease [1][2][3]. In this setting, many plants were studied.…”
Section: Introductionmentioning
confidence: 99%